Quantifying the Risks and Benefits of Continuing Labor Induction: Data for Shared Decision-Making - Teal, Elizabeth Nicole; Lewkowitz, Adam K.; Koser, Sarah L.P.; Tran, Carol B.N.; Gaw, Stephanie L. (American Journal of Perinatology, 2020)
Objective This study aimed to quantify the relative maternal and fetal risks and benefits of continuing labor induction.Study Design This retrospective cohort study included nulliparous women with nonanomalous, singleton, vertex, term pregnancies undergoing labor induction with intact membranes at a tertiary-care academic hospital from January 2015 to April 2017. The primary outcome was mode of delivery. Secondary outcomes included hemorrhage, transfusion, infection, and composite neonatal morbidity. The data were analyzed using chi-square and Fisher's exact tests. Multivariable regression was used to control for potential confounders.Results A total of 955 patients met the inclusion criteria. The median induction duration was 32.3 hours (interquartile range: 20.4–41 hours) and the vaginal delivery rate was 70.5% (n = 673). The chance of vaginal delivery at 12, 24, 36, 48, 60, and ≥60 hours was 76, 83, 77, 74, 72, and 48%, respectively. After controlling for confounders, there was a 20% decrease in chance of vaginal delivery with induction ≥ 24 hours compared with induction < 24 hours. The adjusted relative risks of hemorrhage, transfusion, and infection with induction ≥ 24 hours compared with induction < 24 hours were 1.9, 2.2, and 2.7, respectively (95% confidence interval [CI] of 1.4–2.5, 1.1–3.9, and 1.8–4.0, respectively). The relative risk for these outcomes remained stable or decreased at each subsequent time point. The increasing risks of hemorrhage and infection were primarily among patients who underwent cesarean delivery. There was no association between induction duration and neonatal morbidity.Conclusion In this cohort, the chance of vaginal delivery remained nearly 50% even when induction extended beyond 60 hours. Risks of hemorrhage and maternal infection rose modestly over time, but primarily in patients who underwent cesarean delivery. There was no difference in the risk of transfusion beyond 24 hours and no association between induction duration and neonatal morbidity. These findings may be useful when engaging patients in shared decision-making during labor induction.
Keywords: induction of labor; labor induction duration; prolonged IOL; obstetrics; outcomes; perinatal outcomes; pregnancy; shared decision-making